Violette around the world. 1., My head in the clouds! - Radice, Teresa (EuroComics, an imprint of IDW Publishing, 2018)
"Meet Violette, a curious 12-year-old girl who travels the world with the Cirque de la Lune--the Circus of the Moon, where her mother is the human cannonball and her father is the insect trainer"--Back cover.